2021
DOI: 10.1016/j.esxm.2020.100315
|View full text |Cite
|
Sign up to set email alerts
|

Male Circumcision Due to Phimosis as the Procedure That Is Not Only Relieving Clinical Symptoms of Phimosis But Also Improves the Quality of Sexual Life

Abstract: Introduction Male circumcision is recognized as the most effective method of phimosis treatment. Analyzing the literature, the information about the influence of male circumcision due to phimosis for patients' subjective symptoms such as itching, burning, penile pain, pain during intercourse, and quality of sexual life is insufficient. Aim To investigate the effect of male circumcision due to phimosis to patients' subjective symptoms, including erectile function and sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…Czajkowski et al published the results from a prospective study on 69 patients undergoing circumcision. In this study, 3 months after surgery, all patients achieved significant improvement in both obtaining and maintaining an erection based on IIEF-5 score; moreover, there was an improvement in satisfaction with genital self-image, as confirmed by MGSIS-7 score (15). In our study, only IIEF-5 score showed a statistically significant improvement after treatment, while MGSIS-7 score did not show any improvement compared to the baseline.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Czajkowski et al published the results from a prospective study on 69 patients undergoing circumcision. In this study, 3 months after surgery, all patients achieved significant improvement in both obtaining and maintaining an erection based on IIEF-5 score; moreover, there was an improvement in satisfaction with genital self-image, as confirmed by MGSIS-7 score (15). In our study, only IIEF-5 score showed a statistically significant improvement after treatment, while MGSIS-7 score did not show any improvement compared to the baseline.…”
Section: Discussionsupporting
confidence: 51%
“…Regarding the subjective and objective assessment using patients self-reported information and questionnaires on various domains of sexual function, about 15% of the patients reported an improvement in erectile function and ejaculation time. The theory that phimosis resolution may help the patient to live his sexuality with less stress and anxiety leading to the improvement in erectile and ejaculatory functions was already proposed by several authors who showed the positive effect on sexual life in patients who undergone circumcision due to better erectile function and positive genital self-image (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…When this happening, the remedy method was to remove the suturing nail 3-4 cm near the penile frenulum and resew the wound with silk to correct the unsatis ed realignment of frenulum cut. If not, even if this does not affect the physiology function in most cases, it does affect the penis physical appearance and sexual psychological sometimes, both the patient and their sexual partner, occasionally induce the algopareunia [5]. We reported the morphological classi cation of the frenulum in Chinese individules.…”
Section: Introductionmentioning
confidence: 92%
“…In this way, the quality of the Randomized Clinical Trials, Systematic Reviews and Meta-Analyses regarding the quality of the sex life in patients affected by phimosis following a circumcision and in those not circumcised can be improved. Furthermore, this classification, in defining more homogenous sub-groups, can contribute to identifying and better characterizing the cause-effect relationship for impor- tant diseases, such as cancer of the penis (16)(17). In fact, although there is a lot of evidence demonstrating this relationship, such as the different lifetime risks of penile cancer in circumcised men (1 in 50.000-120.000) (17)(18) and in those uncircumcised (1 in 600-900) (19) and the observation that the benefits of the circumcision are greater if the surgery is done precociously (20).…”
Section: Possible Developmentsmentioning
confidence: 99%